Photodimerisation of the α′-polymorph of ortho-ethoxy-trans-cinnamic acid occurs via a two-stage mechanism at 343 K yielding 100% α-truxillic acid. Issue 38 (13th July 2016) - Fernandes, M. A.; Levendis, D. C.
Abstract : Solid-state photodimerisation of o -ethoxy- trans -cinnamic acid at 343 K (α′ polymorph) proceeds to 100% conversion via a unique two-stage mechanism, both "Schmidt like" and "Kaupp like". Abstract : Three different polymorphs of o -ethoxy- trans -cinnamic acid (OETCA) are known to behave quite differently when irradiated with ultraviolet light. While the α and β polymorphs photodimerise to yield ethoxy-truxillic acid and ethoxy-truxinic acid respectively, the γ polymorph is unreactive. A fourth polymorph, α′, can be obtained by heating the α polymorph to 333 K and stabilising it by partially reacting it. This polymorph contains two distinctly different reaction sites in a 2 : 1 ratio. Irradiation of the stabilised α′ polymorph at 293 K yielded an ordered single crystal product that went to 67% completion (corresponding to the ratio of the different reaction sites). Here we report on the reaction of the α′-polymorph at a higher temperature, 343 K, which now occurs in two separate stages. In stage 1, only molecules in one of the sites react (in a single-crystal-to-single-crystal manner in a similar way to that of the 293 K reaction). In stage 2 the crystal undergoes a phase transition to a polycrystalline phase in which molecules in the second site react, driving the reaction to 100% completion. The powder X-ray diffraction pattern of the final product corresponds to the calculated pattern of the recrystallized ethoxy-truxillic acid photodimer. Examination of close contacts in the crystal structure after stage 1 of the reaction, and using lattice energy calculations to evaluate different arrangements of molecules in the crystal after stage 1, reveals that the reaction occurs in an ordered and cooperative manner even though the product solves as a disordered structure.